A New Regularization Method for a Class of Ill-Posed Cauchy Problems - Tuan, Nguyen Huy; Trong, Dang Duc; Quan, Pham Hoang (Sarajevo Journal of Mathematics, 2024)
In this paper, the Cauchy problem for the elliptic equation is investigated. We use a quasireversibility method to solve it and present convergence estimates under different assumptions for the exact solution. Some numerical tests illustrate that the proposed method is feasible and effective. 2000 Mathematics Subject Classification. 35K05, 35K99, 47J06, 47H10